Comparison of Performance TCP Protocol Over Broadband Hybrid Satellite - เนตรหาญ, วัชรากรณ์ (Journal of Food Health and Bioenvironmental Science, 2019)
This paper compares the protocol of the Transport Control Protocol Tahoe (TCP Tahoe), Transport Control Protocol New Reno (TCP New Reno) and Transport Control Protocol Westwood (TCP Westwood) in the satellite hybrid network. The protocol is an important mechanism to control network communications at the Transport layer since satellite broadband hybrid is a trend of Next Generation Communications System satellite communications. The simulation results in the satellite structure operating in Low Earth Orbit (LEO) simulation showed the evaluation operations included Propagation End-to-End delay of TCP, Tahoe TCP, New Reno, and TCP Westwood with average errors of 1% were below 109 ms, 130 ms, and 199 ms, respectively. In the throughput of TCP Westwood TCP, New Reno, and TCP Tahoe, the average errors of 1% were below 1747599 bps, 1147631 bps, and 964336 bps, respectively. TCP Westwood was the most valuable. Each protocol TCP used network simulator NS - 2 (NS-2). The result of the simulation comparing the effectiveness of the protocols showed the TCP Westwood throughput value was higher and the Propagation End-to-End delay was acceptable for satellite communication systems. Therefore it is suitable to use TCP Westwood in satellite communication systems.